Plant expression systems for production of recombinant pharmaceutically important proteins - E. V. Deineko; A. A. Zagorskaya (Вавиловский журнал генетики и селекции)
The market of pharmaceutically valuable proteins is the fastest growing segment of the economy. Most biopharmaceuticals have been obtained in mammalian and microorganism cells, but both systems have a number of disadvantages. Plant cells combine the advantages of the eukaryotic system of protein production and the simplicity and cheapness of the bacterial, and the use of plants for the production of recombinant proteins is an economically important and promising direction. The advantage of plant systems is the lower cost of cell cultivation. They are free from unwanted components, such as bacterial endotoxins, hyperglycosylated proteins produced by yeast, animal and human pathogens in cell cultures of transgenic animals. In addition, plants are higher eukaryotes, and therefore fullvalue folding and the formation of multimeric protein complexes occur in their cells, as well as a significant portion of posttranslational modifications similar to those in mammalian cells. The currently developed plant expression systems for recombinant proteins are extremely diverse and number more than 100 different technologies based on different plant species, gene transfer methods, expression strategies, methods for the subsequent extraction of the target protein, etc. This is nuclear and plastid transformation, transient and stable expression during transformation using agrobacterial transport, bombardment or electroporation, cultivation of whole terrestrial or aquatic plants, plant tissues or suspension cell cultures as expression systems. The review examines the current state of research in the use of plant expression systems for the production of recombinant proteins for pharmaceuticals. The emphasis was placed on the advantages of plant cell cultures in comparison with other expression systems. Specific examples discuss promising plant systems for the production of recombinant proteins, such as transplastomic plants, moss and aquatic plant cultures, as well as suspension cultures of cells of higher plants. The current state of the market for recombinant proteins obtained using plant expression systems is considered. The prospects of creating plant (“edible”) vaccines based on genetically modified plants are discussed.